From Macromolecular to Small‐Molecular Triggers: Facile Method toward Photoinduced LCST Phase Behavior of Thermoresponsive Polymers in Mixed Ionic Liquids Containing an Azobenzene Moiety. Issue 23 (22nd September 2016) - Wang, Caihong; Ma, Xiaofeng; Kitazawa, Yuzo; Kobayashi, Yumi; Zhang, Shiguo; Kokubo, Hisashi; Watanabe, Masayoshi
Abstract : Instead of the reported photoinduced lower critical solution temperature (LCST) phase transition behavior in ionic liquids (ILs) achieved by photofunctional polymers, this study reports the facile photoinduced LCST phase behavior of nonfunctionalized polymers (poly(benzyl methacrylate) (PBnMA) and poly(2‐phenylethyl methacrylate) (PPhEtMA)) in mixed ILs (1, 3‐dimethylimidazolium bis(trifluoromethanesulfonyl)amide; [C1 mim][NTf2 ] and a newly designed functionalized IL containing an azobenzene moiety (1‐butyl‐3‐(4‐phenylazobenzyl)imidazolium bis(trifluoromethanesulfonyl)amide; [Azo][NTf2 ])) as a small‐molecular photo trigger. Interestingly, the length of the alkyl spacer between the ester and aryl groups, which is the only structural difference between the two polymers, leads to two different photoresponsive LCST phase transition behaviors. On the basis of spectroscopic studies, the different phase transition behaviors of PBnMA and PPhEtMA may attribute to the different cooperative interactions between the polymers and [C1 mim][NTf2 ]. Abstract : A photoresponsive ionic liquid ([Azo][NTf2 ]) is synthesized and successfully used as a small‐molecular trigger to control the photoinduced phase transition behavior of thermoresponsive polymers in ionic liquids. Poly(2‐phenylethyl methacrylate)‐based mixtures rich in cis ‐[Azo][NTf2 ] show lower clouding temperatures than those rich in trans ‐[Azo][NTf2 ], while poly(2‐benzyl methacrylate) exhibits opposite trends.